Involvement in Terrorist Offenses and Public Appeals for Terrorist Activity: Issues of Differentiation - D. K. Bokov (Actual Problems of Russian Law, 2026)
The paper proves that significant differences in the criminogenic potential (and, as a consequence, in the public danger) of involvement in the commission of terrorist crimes (Part 1, 11 of Article 2051 of the Criminal Code of the Russian Federation) and public appeals for terrorist activity (Article 2052 of the Criminal Code of the Russian Federation) are primarily associated with the level of specificity of the relevant statements, with the degree of their detail. Psychological and linguistic research confirms that calls to specific actions and setting instrumental tasks that are easy to imagine and plan have a much greater motivational effect than general incentive statements. These patterns also apply to criminal recruitment: encouraging individuals to commit a specific terrorist crime with a description of its details (type of crime, sequence of criminal actions, time, place, etc.) has an incomparably greater motivating effect than general calls for terrorist activity. The specific nature of instigation, as provided for in Parts 1 and 11 of Article 2051 of the Criminal Code of the Russian Federation, is that the recruiter incites another person to commit a terrorist crime (specification), while detailing the essential individual characteristics of the future crime (factual specification). This distinguishes it from public appeals for terrorist activity, for which such specification is not characteristic.